2020
DOI: 10.1038/s41598-020-69003-0
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of gamma radiation dose rate related with natural radionuclides in all of Vietnam and radiological risk assessment of the built-up environment

Abstract: A built-up environment utilizes building materials containing natural radionuclides that will change radiological risks. While radiological risks have been estimated from the activity concentrations of natural radionuclides in soil, it is important to evaluate the changes of these risks for the built-up environment using these building materials. Based on the direct measurements of absorbed dose rate in air and calculation of absorbed dose rate in air from activity concentrations in soil for all of Vietnam whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 27 publications
(37 reference statements)
2
16
0
Order By: Relevance
“…This result is approximately 46% higher than the experimental analysis made by El-Taher (2012), which found a value of 25.08 nGy h −1 for the granite used as building materials in Qassim area of Saudi Arabia. Inoue et al (2020) found that the average absorbed dose rate in air for all Vietnam, due to natural radionuclides such those considered in the present work, was 75 ± 32 nGy h −1 , with values varying from 8 -463 nGy h −1 . Table 5 presents the annual effective dose rate contribution for different radionuclides and for different virtual phantoms, which were obtained based on the dose rate in air and the CC [E] values.…”
Section: Table 4 CC [Hsupporting
confidence: 45%
“…This result is approximately 46% higher than the experimental analysis made by El-Taher (2012), which found a value of 25.08 nGy h −1 for the granite used as building materials in Qassim area of Saudi Arabia. Inoue et al (2020) found that the average absorbed dose rate in air for all Vietnam, due to natural radionuclides such those considered in the present work, was 75 ± 32 nGy h −1 , with values varying from 8 -463 nGy h −1 . Table 5 presents the annual effective dose rate contribution for different radionuclides and for different virtual phantoms, which were obtained based on the dose rate in air and the CC [E] values.…”
Section: Table 4 CC [Hsupporting
confidence: 45%
“…Therefore, the coal demand and consequently, the amount of fly ash and slag discharged into the environment from Vinh Tan CFPPs might be higher than those from Duyen Hai CFPPs. The previous study of Inoue et al (2020) 26 also showed that the absorbed dose rate (65 nGy h −1 ) in Binh Thuan province was higher than the corresponding value (54 nGy h −1 ) in Tra Vinh province.…”
Section: Discussionmentioning
confidence: 74%
“…The dose rate refers to the intensity of the radionuclides stored in every part of the tissue situated at every location of the body (Inoue et al, 2020). Inoue at al.…”
Section: Absorbed Dose Rate (Adr)mentioning
confidence: 99%
“…The dose rate refers to the intensity of the radionuclides stored in every part of the tissue situated at every location of the body (Inoue et al, 2020). Inoue at al. (2020) emphasized that the ADR is the basis upon which damages done to the tissues or organs of humans can be estimated.…”
Section: Absorbed Dose Rate (Adr)mentioning
confidence: 99%